Chitosan and Chitosan/Titania Beads for Reactive Red 35 Removal (Journal of Fiber Bioengineering and Informatics, 2016)
This study investigated the adsorption capacity to remove C.I. Reactive Red 35 by three differentadsorbent beads, consisting of pure chitosan and two different chitosan ⁄ titania (TiO2) composite beadswith the TiO2 being obtained either from the sol-gel method or from added commercial TiO2 (A100-TiO2). From the obtained dye adsorption capacities, the chitosan ⁄ TiO2 composite beads with A100-TiO2 had the highest adsorption ability to remove reactive dye solution up to 97%, compared to thechitosan ⁄ TiO2 composite beads with TiO2 obtained from the sol-gel method (adsorption capacity of 70-45%). This maybe because the A100-TiO2 contained in the chitosan ⁄ TiO_2-sol composite beads was in theanatase crystalline form, while the TiO2 obtained from the sol-gel method did not form a good anatasecrystalline form, as shown by X-ray diffraction patterns and SEM micrographs. The crystallization ofanatase formed in the composite beads enhanced the adsorption capacity of the composite beads. Purechitosan adsorbent also showed a good adsorption capacity (95%) due to the electrostatic interactionsbetween chitosan and C.I. Reactive Red 35.